Responding to the global challenges for a food secure future - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Live from Agriculture and Rural Development Day at Rio+20, 18 June 2012 http://www.agricultureday.org Speakers: - Addressing gender equity in access to natural resources -- Rajendra S. Paroda, Executive Secretary, Asia-Pacific Association of Agricultural Research Institutions (APAARI) - Strategic partnership -- Mark Holderness, Executive Secretary, Global Forum on Agricultural Research (GFAR) - Securing long-term funding -- Jonathan Wadsworth, Executive Secretary of the CGIAR Fund Council and Head of Fund Office - Agrobiodiversity -- Alexander Mueller, Assistant Director General for Natural Resources, Food and Agriculture Organization of the United Nations (FAO) - Household nutrition security -- Cristina Tirado, Director, Center for Public Health and Climate Change, Public Health Institute (PHI) - Integration through a Landscape Approach -- Frances Seymour, Director General, Center for International Forestry Research (CIFOR) Join the discussion: #rio4ag http://www.twitter.com/agricultureday http://www.facebook.com/agricultureday